Maximizing Solar Power Penetration in Off-grid Rural Areas: A Case Study on 200kWp PV-Diesel Hybrid - Hartadhi Hartadhi; Kholid Akhmad; Riza Riza (JAREE (Journal on Advanced Research in Electrical Engineering), 2018)
In rural and isolated island, electric power on the island as an off-grid system is typically supplied by diesel generators (DGs) and Solar Power Plant. The paper proposes options to maximize PV penetration in the hybrid system with minimum modification to the existing system. Modified HOMER simulation modeling is used to mimic the behavior of hybrid PV-Diesel controller. Existing DGs configuration and current load profile shall be taken into account in these options. Maximized PV penetration will decrease fossil fuel dependency, lower LCOE, reduce carbon emission and further support the government's National Energy Policy (NEP) program in renewable energy. Keywords: Microgrid, Smartgrid, HOMER, Photovoltaic, Diesel, Hybrid, Solar Power Plant, Renewable Energy